2010
DOI: 10.1111/j.1471-4159.2010.06854.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of markers of synaptic function in mouse models of depression: chronic mild stress and decreased expression of VGLUT1

Abstract: 1These authors contributed equally to this study.Abbreviations used: Arc, activity regulated cytoskeletal protein; BDNF, brain derived neurotrophic factor; CMS, chronic mild stress; DG, dentate gyrus; FST, forced swimming test; IEG, immediate early gene; PBS, phosphate-buffered saline; SSC, saline sodium citrate buffer; SVP, synaptic vesicle protein; VGLUT1, vesicular glutamate transporter 1; WT, wild type. AbstractDepression has been linked to failure in synaptic plasticity originating from environmental and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 59 publications
4
37
1
3
Order By: Relevance
“…The principal finding of the current study is that administration of a VGLUT1-targeting lentiviral shRNA vector into the dorsal hippocampus of Targeting whole-brain VGLUT1 expression using conventional gene knockout strategies results in a 35-41% decrease in transporter levels in heterozygous animals (Tordera et al, 2007;Garcia-Garcia et al, 2009). These mice exhibit anxiety and a 'depressive-like' phenotype accompanied by deficits in working, social, and visual recognition memory and impaired PPI, reversal learning, fear extinction, and hippocampal long-term potentiation (Tordera et al, 2007;Garcia-Garcia et al, 2009;Balschun et al, 2010;Elizalde et al, 2010;Inta et al, 2012;Callaerts-Vegh et al, 2013). The latter is consistent with the fact that VGLUT1 localizes to synapses with low release probability (that exhibit long-term potentiation), whereas VGLUT2 localizes to synapses with high release probability (that exhibit longterm depression; Varoqui et al, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…The principal finding of the current study is that administration of a VGLUT1-targeting lentiviral shRNA vector into the dorsal hippocampus of Targeting whole-brain VGLUT1 expression using conventional gene knockout strategies results in a 35-41% decrease in transporter levels in heterozygous animals (Tordera et al, 2007;Garcia-Garcia et al, 2009). These mice exhibit anxiety and a 'depressive-like' phenotype accompanied by deficits in working, social, and visual recognition memory and impaired PPI, reversal learning, fear extinction, and hippocampal long-term potentiation (Tordera et al, 2007;Garcia-Garcia et al, 2009;Balschun et al, 2010;Elizalde et al, 2010;Inta et al, 2012;Callaerts-Vegh et al, 2013). The latter is consistent with the fact that VGLUT1 localizes to synapses with low release probability (that exhibit long-term potentiation), whereas VGLUT2 localizes to synapses with high release probability (that exhibit longterm depression; Varoqui et al, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…If major depression is due to lack of reward, the analysis of molecular profiles in the nucleus accumbens from CUMS‐induced depression and resilience should help to figure out the role of the nucleus accumbens in major depression and resilience based on molecules analyzed. The alternations of certain genes have not been observed in previous analyses (Bai et al, 2014; Elizalde et al, 2010; Li et al, 2013; Liu et al, 2015; Moreau, Bruse, David‐Rus, Buyske, & Brzustowicz, 2011; Rajkowska et al, 2015; Smalheiser et al, 2012, 2011, 2014), including Cckar , Tshr , Kcnj5 , Alox12 , Slc17a6 , Per2 , Rtn4r , and Nrn1 . These genes in the nucleus accumbens may be newly working for major depression or resilience.…”
Section: Discussionmentioning
confidence: 80%
“…CVS chronic variable stress The CVS procedure was developed as an animal model of depression that presents three important characteristics: the inducing conditions are relatively realistic, the focus of the model is a core symptom of depression, anhedonia, and the protracted time course of the model is suitable for investigating the effects of chronic drug treatments [31]. A series of publications have reported that the CVS procedure causes decreased intake of sucrose solutions (or pellets) [32][33][34][35], impairments in other measures of hedonic reactivity such as place preference conditioning [36,37] and brain stimulation reward [38,39], decreased sexual and aggressive behaviors [40,41] and self-care [42][43][44], in addition to changes in sleep architecture [39,45]. Moreover, these behavioral changes are reversed by chronic treatment with all classes of clinically-effective antidepressant drugs, but not by drugs known to be ineffective as antidepressants.…”
Section: Discussionmentioning
confidence: 99%